Four new species of Ampharetidae (Annelida: Polychaeta) from Pacific hot vents and cold seeps, with a key and synoptic table of characters for all genera - Reuscher, Michael; Fiege, Dieter; Wehe, Thomas (Zootaxa, 2009)
Four new species of the polychaete family Ampharetidae are described from hot vents and cold seeps in the Pacific. Amage benhami sp. nov., Amphisamytha vanuatuensis sp. nov., Anobothrus apaleatus sp. nov., Glyphanostomum holthei sp. nov. For Amphisamytha vanuatuensis sp. nov., different stages in the development of branchiae are described. While this species was found in the Western Pacific, A. galapagensis is presumed to be restricted to the Eastern Pacific with Amphisamytha fauchaldi being a junior synonym. A key to members of the genera Amphisamytha and Glyphanostomum, and synoptic tables of characters for all members of the genera Amphisamytha and Anobothrus are provided. A key and synoptic table of characters comprising all genera of the Ampharetidae is also given together with a discussion of taxonomic problems within the subfamily Ampharetinae in order to clarify the taxonomy of the group. An additional table contains special information on all genera within the Ampharetinae, which show dorsal modifications on some segments.